A Review of Customer Loyalty: An emperical study at CV Bintang Jaya Abadi - Nora Sari Liandy (Indonesian Journal of Business Analytics, 2021)
The number of different types of businesses that are starting to emerge in Indonesia shows that business development is now accelerating. As a result of the recent increase in the number of enterprises, a lot of businesses will confront strong rivalry in every aspect of their operations in today's market. As a result, every company must be adept and compete fiercely when dealing with competition. However, the predominant problem that could effects the company sustain is through there product quality, customer perception of price as well as customer satisfaction which could effect the customer loyalty. In aim to learn more about this issue, this research is intended to investigate the effects of product quality, perception of price and customer satisfaction on customer loyalty at CV Bintang Jaya Abadi, Medan. By using a quantitative approach, the sampling method is done by using the Lemeshow formula. Thus, the samples that were taken are 96.04 = 100 respondents. In analyzing all the data, SPSS 25.0 was being conducted in this research and the data was collected by distributing online questionnaires, the data measurement used the 5-point Likert scale to measure all (19) indicators. Besides that, multiple linear regression analysis was utilized in this reseacrh. Based on the results of this research, it shows that the Product quality (X1) and Customer Loyalty (Y) variables have negative and no significant effect. However, Perception of Price (X2), Customer Satisfaction (X3) and Customer Loyalty (Y) variables have positive and significant effect.